Academic Exclusion: Some Experiences - Arye L. Hillman; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2016)
We describe and compare the experiences of academic exclusion of Alexander Del Mar, J.A. Hobson, and Gordon Tullock. While aspects of the circumstances differed, a common element was academic exclusion because of challenges to mainstream views. Alexander Del Mar, J.A. Hobson, and Gordon Tullock were in due course recognized for the originality and merit of their contributions, although each incurred personal costs because of the exclusion by the academic elites of their time. Our study takes us into the role of ideologically based prejudice in judgement of the worthiness of economic ideas.
Keywords: A11; A14; B31; H11; P16; 330; ideology; rents; rent seeking; X-efficiency; Gordon Tullock; Alexander Del Mar; J.A. Hobson; bias; eugenics; prejudice; anti-Semitism; professional recognition; strategic referencing